Initial Interaction Expectations with Robots: Testing the Human-To-Human Interaction Script. Issue 2 (14th March 2016) - Edwards, Chad; Edwards, Autumn; Spence, Patric R.; Westerman, David
Abstract : As social robotics becomes more utilized and routine in everyday situations, individuals will be interacting with social robots in a variety of contexts. Centered on the use of human-to-human interaction scripts, the current study hypothesized that individuals would be more uncertain, have less liking and anticipate less social presence when they are told that they will be interacting with a social robot as opposed to another person. Additionally, the current study utilized a two-time measurement model experiment to explore perceptions of interacting with either a robot or human. Data were consistent with hypotheses. Research questions examined perceptions from Time 1 to Time 2 for the robot condition on the dependent variables. Findings are discussed in light of future research studies.